Care Case Managers’ Job Satisfaction: a first contribution to the Italian validation of the Job Satisfaction Scale - Foà, Chiara; Bertinelli, Simona; Boschini, Anna; Fragnelli, Maria; Svichkar, Valentina; Tempone, Maria Rosaria; Sarli, Leopoldo; Giovanna Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2016)
Background and aims of the work: From the analysis of the Italian literature emerges a lack of studies both about the work satisfaction of Case Care Manager Nurses (CCMN) and on their role in the sanitary context. This research aims to fill this gap through a first Italian validation of the Job Satisfaction Scale (JSS). Method: An Italian translation of JSS was provided by three independent judges. To verify the convergent validity of the scale the McCloskey Mueller Satisfaction Scale were used. A measure of the Organizational Wellbeing in the Operating Unit was used in order to verify the concurrent validity. A Professional Self-Efficacy evaluation allowed to verify the discriminant validity. Two open questions examined the role description and the difficulties met at work by the CCMN. The questionnaire was published on the Italian Association of Case Manager and in several Italian Professional Associations of Nurses, Sanitary Assistants and Pediatric nurses (IPASVI). Results: 86 people (70 women) answered the questionnaire; 34 of which were Nurses and 52 CCMN. The convergent, the discriminant and the concurrent validity of the scale were proved. The participants were more satisfied with the quality and the kind of their job, and with the supervision and the colleagues, and less satisfied with the contingent recognitions, the marginal benefits, the promotions and with working and salary conditions. No relevant differences were found between Nurses and CCMN, but in authonomy, responsibility and professional opportunities the CCMN were more satisfied. Conclusions: This study aimed to offer a first validation contribution of the JSS Scale. Unfortunately the number of participants did not allow to testify a confirmatory factor analysis of the scale. Thus this work should be further improved. Finally, the data highlighted the need to investigate on the recognition of CCMN, since its absence is often the cause of a job dissatisfaction.